Kinematic analysis of butterfly turns of international and national swimmers - Tourny-Chollet, C.; Chollet, D.; Hogie, S.; Papparodopoulos, C. (Journal of Sports Sciences, 2002)
The aims of this study were (1) to evaluate the different turn phases of 200 m butterfly during competition in a 50 m pool, (2) to determine if wall contact times are related to swim speed and (3) to compare the turn variables of a European Champion with other swimmers. In the first part of the study, we assessed the turns of 22 swimmers ranked in three groups according to 200 m butterfly swim performance (fast group = 121.73+/-3.03 s, intermediate group = 126.25+/-0.55 s, slow group = 129.24+/-2.30 s). Two turn times were recorded: the first before the turn (i.e. the time it takes the swimmer's head to reach the wall from 7.5 m away) and the second after the turn (i.e. the time from the wall to the point at which the swimmer's head passes 7.5 m away). The third turn was performed significantly faster by the fast group than by the slow group, both before (P< 0.01) and after (P< 0.02) the turn. In the second part of the study, objectives (2) and (3) were evaluated among 15 swimmers based on a specific protocol. Three cameras (50 Hz) simultaneously recorded the turn; these were placed above the water 10 m before the wall, 5 m before and just above the wall. Longer contact times of the feet on the wall were associated with a faster push-off speed (P < 0. 02). The European Champion achieved an improved contact time while performing a rapid pull-out speed.